Solitary Rectal Ulcer Syndrome in a 12-Year Bangladeshi Boy: an Unusual Cause of Rectal Bleeding (KYAMC Journal, 2020)
Solitary rectal ulcer syndrome (SRUS) is an uncommon cause of per rectal bleeding in children. Due to it's wide variety of presentation and rarity, it is frequently misdiagnosed as other clinical condition like inflammatory bowel disease, rectal polyp, amoebiasis or malignancy. Here we presenting a case initially misdiagnosed as ulcerative colitis, latter after thorough evaluation diagnosed as a case of SRUS.KYAMC Journal Vol. 11, No.-2, July 2020, Page 104-107